Detecting Demyelination by PET: The Lesion as Imaging Target. (19th July 2018) - Brugarolas, Pedro; Reich, Daniel S.; Popko, Brian
Noninvasive imaging of demyelination and remyelination is critical for diagnosis and clinical management of demyelinating diseases. Positron emission tomography (PET) has the potential to complement magnetic resonance imaging (MRI) by providing a quantitative measure specific to demyelination. In Brugarolas et al's study 1, we describe the development of the first PET tracer for voltage-gated K + channels based on a clinically approved drug for multiple sclerosis that can be used for imaging demyelination in animal models.